The biology of the eye - Fischbarg, Jorge; ScienceDirect eBooks (Amsterdam ; Boston ; Oxford : Elsevier, 2006)
Explores the many novel ideas about the eye in a systematic and synthetic way. This work includes both basic sciences and applications towards clinical research. It contains chapters that include both anatomical and functional descriptions of different ocular tissues. It is suitable to students in basic biomedical science, and ophthalmologists.
Preface / Jorge Fischbarg -- Why the eye is round / Larry S. Liebovitch -- Tears and their secretion / Darlene A. Dartt, Robin R. Hodges and Driss Zoukhri -- The cornea : epithelium and stroma / Niels Ehlers and Jesper Hjortdal -- The corneal endothelium / Jorge Fischbarg -- Ciliary body and ciliary epithelium / Nicholas A. Delamere -- The lens / Guido A. Zampighi -- The vitreous / Henrik Lund-Andersen [and others] -- The retina / Morten la Cour and Berndt Ehinger -- The retinal pigment epithelium / Morten la Cour and Tongalp Tezel -- The choroid and optic nerve head / Jens Folke Kiilgaard and Peter Koch Jensen -- Innate and adaptive immunity of the eye / Mogens Holst Nissen and Carsten Röpke -- Drug delivery to the eye / Ashim K. Mitra, Banmeet S. Anand and Sridhar Duvvuri -- The sclera / Klaus Trier.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Eye -- Physiology; Eye -- Anatomy; Eye -- Physiology -- Research; MEDICAL -- Neuroscience; PSYCHOLOGY -- Neuropsychology; Ocular Physiological Phenomena; Eye -- anatomy & histology; Eye -- Anatomy; Eye -- Physiology; Electronic books